Resosialisasi di lembaga pemasyarakatan khusus anak - Sri Haryaningsih; Titik Hariyati (Jurnal Konseling dan Pendidikan, 2020)
A child in conflict with the law is defined as a child who is undergoing a punishment process and is 12-18 years old and is not married. Based on data from the Directorate General of Corrections (Ditjen PAS) of the Ministry of Law and Human Rights in 2019, it was recorded that 56 cases of children had received court decisions. The purpose of this study was to determine the patterns of child growth and development and the factors that influence the development of children in the Penitentiary of West Kalimantan Province. This research is a qualitative research with research subjects are childrens at the Institute for Special Development for Children (LPKA). This research was conducted with structured interviews and observations of child prisoners in LPKA. Data analysis was carried out in the following stages, namely data reduction, data triangulation and data presentation and drawing conclusions/verification. The results found that the development of child prisoners in LPKA was not yet effective. The factors that influence child development are facilities, infrastructure and psychological aspects of the child.